The Impact of English Educational Tourism on the Growth of Local Economy: A Systematic Literature Review - Muhammad Basri; Farzana Sharmin Pamela Islam; Muhammad Azwar Paramma; Ismail Anas (International Journal of Language Education, 2023)
This systematic literature review (SRL) examines the impact of English educational tourism (EET) on the growth of local Small-Medium Enterprises (SMEs). Through a comprehensive search of academic databases and systematic assessment of study quality, a total of 49 studies were selected for inclusion. The studies varied in design, location, and intervention, but all focused on the relationship between English educational tourism and the growth of local SMEs. This SLR focuses on the typology of SMEs in EET, its impact on rural economy and local community empowerment, and SMEs’ challenges in growing their businesses. The findings suggest that English educational tourism can have a positive impact on local SMEs and rural communities, including increased revenue, community empowerment, cultural preservation, and poverty reduction. However, it is crucial to ensure that the benefits of EET are distributed fairly and that local communities are actively involved in the decision-making process to maximize positive impacts and mitigate potential negative impacts. Overall, the results suggest that English educational tourism can be a promising strategy for promoting the growth of local economy, but more research is needed to fully understand the conditions under which this impact is most effective.